Measurements of correct ice adhesion forces to metal test plates in nano-scale by using SPM. (June 2016) - Matsumoto, Koji; Honda, Masato; Minamiya, Kazuyuki; Tsubaki, Daisuke; Furudate, Yuta; Murase, Masashi
Highlights: Correct ice adhesion force to the metal could not be obtained by past method. Correlations of ice height and diameter for alloys and pure metals were different. Shearing stresses by present work were much larger than those by other works. The magnitude relation of shearing stresses for four metals could be given. Correct ice adhesion forces and shearing stresses of four metals could be given. Abstract: To prevent many problems caused by ice adhesion, its control technology is required. To settle this technology, obtaining the correct ice adhesion force is a key point. However, ice adhesion forces obtained by current conventional methods are apparent values including a force breaking ice. Thus, authors developed a method to measure correct ice adhesion force and accurate ice diameter in a nano-scale by SPM and both for copper were measured. To construct a database to store the correct ice adhesion forces and diameters for various metals, first, the ice adhesion forces and the ice diameters for aluminum, titanium, carbon steel, and stainless steel are measured at −5°C by the SPM. Additionally, to easily compare our results with other works, shearing stresses of the metals are also given by the ice adhesion forces and ice adhesion areas. Validities of our results are proven by comparing them with the surface energies and other works.